2010
DOI: 10.1021/nn101696r
|View full text |Cite
|
Sign up to set email alerts
|

DNA Cleavage System of Nanosized Graphene Oxide Sheets and Copper Ions

Abstract: The exploration of efficient DNA intercalative agents (intercalators) is essential for understanding DNA scission, repair, and signal transduction. In this work, we explored systematically the graphene oxide (GO) interaction with DNA molecules using fluorescence spectroscopic (FL) and circular dichroism (CD) studies, gel electrophoresis, and DNA thermal denaturation. We demonstrated that the GO nanosheets could intercalate efficiently into DNA molecules. Significantly, we illustrated that the scission of DNA b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
109
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(117 citation statements)
references
References 33 publications
8
109
0
Order By: Relevance
“…In line with other reports [1,4,5], this strongly suggested for the coordination of GO's oxygen functionalities to the cupric ions, although ion exchange could not be ruled out [6]. In order to obtain direct molecular-level information on the binding mode of copper, we studied the adsorption of Cu(II) 2,2'-bipyridyl complexes of different compositions on GO by electron paramagnetic resonance (EPR) spectroscopy, supplementing the adsorption and X-ray diffraction (XRD) data.…”
supporting
confidence: 93%
“…In line with other reports [1,4,5], this strongly suggested for the coordination of GO's oxygen functionalities to the cupric ions, although ion exchange could not be ruled out [6]. In order to obtain direct molecular-level information on the binding mode of copper, we studied the adsorption of Cu(II) 2,2'-bipyridyl complexes of different compositions on GO by electron paramagnetic resonance (EPR) spectroscopy, supplementing the adsorption and X-ray diffraction (XRD) data.…”
supporting
confidence: 93%
“…The specific interaction mechanism could be found in Ref. [100]. As it is illustrated, the cleavage efficiency was still low and the concentration of Cu 2+ was high because the size of GO sheets was not well tailored.…”
Section: Dna Cleavagementioning
confidence: 97%
“…They found that graphene oxide at a concentration of 85 μg mL −1 significantly suppresses the growth of E. coli after 2 h incubation at 37°C, with an inhibition rate of over 90 %. In addition, graphene oxide may adsorb metal ions such as Mn +2 and Cu +2 via complexation or chelation on oxygen functional groups [106,152].…”
Section: Biocompatibility Graphene-based Materialsmentioning
confidence: 99%